2000
DOI: 10.1002/1522-2683(20000701)21:13<2641::aid-elps2641>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

A microarray enzyme-linked immunosorbent assay for autoimmune diagnostics

Abstract: In order to quantify autoantibodies in the sera of patients with autoimmune disease, we have created a microarray-based immunoassay that allows the simultaneous analysis of 18 known autoantigens. The microarrays contain serial dilutions of the various antigens, thereby allowing accurate determination of autoantibody titer using minimal amounts of serum. The assay is very sensitive and highly specific: as little as 40 fg of a known protein standard can be detected with little or no cross-reactivity to nonspecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
125
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 0 publications
0
125
0
2
Order By: Relevance
“…The field of protein microarrays currently encompasses applications that include profiling of serum and tissues from cancer patients [6,7], autoimmune diagnostics [8], protein interaction screening [9-12], as well as antibody-based detection of multiple antigens [13-17]. Recent increases in sensitivity and quantitative reproducibility has extended the utility of antibody microarrays [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The field of protein microarrays currently encompasses applications that include profiling of serum and tissues from cancer patients [6,7], autoimmune diagnostics [8], protein interaction screening [9-12], as well as antibody-based detection of multiple antigens [13-17]. Recent increases in sensitivity and quantitative reproducibility has extended the utility of antibody microarrays [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This type of analytical protein array has been used to identify autoimmune diseases and allergens (Joos et al, 2000;Hiller et al, 2002). Joos et al (2000) created a microarray-based immunoassay with 18 antigens to quantify autoantibodies in the sera of patients with autoimmune disease. The protein array technology has been applied to develop a miniaturized allergy test containing 94 purified allergen molecules (Hiller et al, 2002).…”
Section: T W O Classes O F P Ro Tein Arraysmentioning
confidence: 99%
“…produced against the organism's own proteins and epitopes) play an important role in the clinical manifestation of the diseases. Recently, Joos et al [67] reported a micro-array based test for the parallel detection of autoantobodies in human sera. Characterization of autoimmune patient sera on protein chips would allow the diagnosis of autoimmune diseases based upon the presence of specific autoantibodies.…”
Section: Applications Of Protein Arraysmentioning
confidence: 99%
“…Therefore, profiling the antibody repertoire of patients with autoimmune disease is believed to be medically relevant and informative. [67] In contrast to the standard test involving time consuming tissue or cell culture immunofluorescence, only minimal amounts of sera (1μl per sample) are required. For the identification of antigens recognized by autoantibodies, sera from patients with autoimmune disease have been hybridized to uncharacterized λgt11 cDNA phage libraries or to tissue extracts separated by 1D or 2D gel electrophoresis.…”
Section: Applications Of Protein Arraysmentioning
confidence: 99%